Management styles - Khandwalla, Pradip N. (New Delhi ; New York, 1995)
Focuses on the various styles of management. Describes 10 different styles of management and their defects. Highlights certain styles that seem to be associated with superior organizational learning, smoothness of learning, managerial development, synergy, performance etc.
Includes bibliographic references and index.
oif 31/03/15
Loan
Keywords: Management